2013
DOI: 10.1136/bjsports-2012-091961
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of shockwave therapies in soft tissue conditions: focusing on the evidence

Abstract: 23 appropriate studies were identified. There is evidence for the benefit of F-ESWT and of RPT in a number of soft tissue musculoskeletal conditions, and evidence that both treatment modalities are safe. There is evidence that F-ESWT is effective in the treatment of plantar fasciitis, calcific tendinitis, and that RPT is effective in plantar fasciitis. Where benefit is seen in F-ESWT, it appears to be dose dependent, with greater success seen with higher dose regimes. There is low level evidence for lack of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
210
0
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(222 citation statements)
references
References 33 publications
0
210
0
12
Order By: Relevance
“…Three focused on various types of MT 13,17,21 ; 2 on extracorporeal shockwave therapy (ESWT) 34,37 ; and 1 each on transcutaneous nerve stimulation (TENS), 31 taping, 32 multimodal therapies, 46 and exercise. 33 For MT (skilled hand movements performed by a therapist 17 ), manipulation and mobilization were included.…”
Section: Noncalcific Rotator Cuff-associated Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three focused on various types of MT 13,17,21 ; 2 on extracorporeal shockwave therapy (ESWT) 34,37 ; and 1 each on transcutaneous nerve stimulation (TENS), 31 taping, 32 multimodal therapies, 46 and exercise. 33 For MT (skilled hand movements performed by a therapist 17 ), manipulation and mobilization were included.…”
Section: Noncalcific Rotator Cuff-associated Conditionsmentioning
confidence: 99%
“…49 For ESWT, 2 acceptable-quality reviews both found that ESWT was not effective for noncalcific rotator cuff tendinitis. 37,49 For TENS, a high-quality review found that because of the scarcity of evidence and high risk of bias of existing studies, no conclusions could be made about its effectiveness. 31 For taping, an acceptable-quality review found that the evidence for taping alone or with other therapies was insufficient to make a conclusion.…”
Section: Noncalcific Rotator Cuff-associated Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentre eles destacamse o ultrassom terapêutico, as ondas de choque extracorpóreas e o exercício de fortalecimento muscular excêntrico (EFE) 16 . Como parte do tratamento fisioterapêutico a literatura tem sugerido o EFE com eficaz na resolução de tendinopatias 7,17,18,19,20,21,22 , o mesmo caracteriza-se por alongamento muscular ativo com a utilização de carga 23,24,25 .…”
Section: Resumo | Introduçãounclassified
“…Literatürde lateral epikondilit tedavisinde ESWT ve RESWT'nin uygulandı-ğı çok sayıda çalışma yer almaktadır. Bu çalışmaların bazılarında şok dalgalarının etkili olduğu bulunurken, bazı çalışmalarda ise plasebo uygulamadan farkı olmadığı bildirilmiştir (13). Ayrıca çalışmalar arasındaki metodolojik farklılıklar nedeniyle karşılaştırma yapmak zordur.…”
unclassified